The Effect Of Dragon Fruit Consumption On The Hb Levels Of Mildly Anemic Pregnant Women In Trimester Ii In The Working Area Of The Totokaton Puskesmas, West Tulang Bawang District - Novi Indriani; Juwita Desri Ayu; Yuni Astini; Komalasari, Komalasari (Sean Institute, 2024)
Anemia in pregnancy is partly caused by iron deficiency with an incidence of 62.3%; anemia has negative impacts such as miscarriage, premature labor, bleeding, and shock. For anemia prevention, it is recommended to consume 60mg of Iron and 0.25 folic acid equivalent to 200mg ferrosulfate during pregnancy for a minimum of 90 tablets, in addition to consuming iron-rich foods and vitamin C such as dragon fruit. In 100 grams of dragon fruit contains 63.9 mg of iron and vitamin C. The research aim is to determine the effect of dragon fruit consumption on Hb levels in pregnant women with mild anemia in trimester II in the working area of Totokaton Community Health Center, West Tulang Bawang Regency. This research is a quantitative study with a pre-experimental design using a *one group pretest – posttest design* approach. The population of second-trimester pregnant women was 65 people with a sample of 30 respondents using purposive sampling technique. The research was conducted in the working area of Totokaton Community Health Center in September 2024. Data collection used observation sheets. Analysis was conducted using univariate bivariate (*paired sample t-test*). The research results showed that the Hb levels in pregnant women before being given dragon fruit was 10.2 g/dl and after was 11.1 g/dl. There was an effect of dragon fruit consumption on Hb levels in pregnant women with mild anemia in trimester II (p-value = 0.000). Recommendations for pregnant women with mild anemia to consume dragon fruit as complementary therapy, and for the Community Health Center as a reference for pregnant women with mild anemia, for researchers as application material for knowledge gained. Meanwhile, for the University, it can be used as a reference in the form of scientific work and journal publications, and for future researchers, it can be used as a reference in subsequent research.